(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2022)
Background: Nursing education is stressful for students: an inherent quality of a competitive professional degree program leading to a career where client safety and quality health care are dependent on graduates with high levels of intellectual and emotional capacities. In the interest of student health and well-being, it is worthwhile taking a moment to pause and consider what, if any, stressors can be minimized or eliminated. This study resulted from such a moment of pause to consider norms related to in-person timed written tests and how the factor of time might be contributing to modifiable student stress. Purpose: The purpose of this study was two-fold: 1) to explore nursing students’ experience of double time on all major in-person written tests, and 2) to examine the relationship between the time it takes a student to write a test and their grade on that evaluation measure when double time is provided. Methods: The study involved a mixed-methods descriptive correlational design. Convenience sampling was used to recruit undergraduate nursing students across three pathways within one collaborative bachelor of nursing program over the 2018–2019 academic year. Qualitative data were collected through an online survey to capture the students’ experience of double time on in-person written tests. Quantitative data included the length of time each student took to complete a test in minutes as well as the student’s grade on the test. Results: Thematic analysis of data from completed surveys (n = 457) revealed students’ experience of the calming and enabling impact of having double time for all in-person written tests. Analysis of quantitative data demonstrated lack of a consistent overall difference or relationship between the time a nursing student takes to complete a written test and their grade on that test. Conclusion: Teaching norms related to timed written tests were questioned in the interest of enhancing the quality of the student experience. The findings of this study provide preliminary evidence that offering a double time option for in-person written tests may help create the learning environment needed to mitigate an important element of nursing student stress and enhance the quality of their academic experience.